Analysis of Students' Critical Thinking Skills Improvement in Static Fluid Material - Syarifah Mudaimah Awwaliyah; Muhammad Minan Chusni (International Journal of Science, Technology and Applications, 2025)
This study stems from the problem of students' low critical thinking skills in physics learning, particularly in static fluid material. This study aims to analyze the level of students' critical thinking skills based on critical thinking indicators. The researcher positioned himself as an observer who examined students' critical thinking skills through a quantitative approach with a descriptive method. Data collection was carried out using an essay test compiled based on critical thinking skill indicators, namely elementary clarification, basic support, inferring, advanced clarification, and strategy and tactics. Supporting data were obtained through observation and interviews to strengthen the analysis results. Data were analyzed by calculating the average value for each indicator and categorizing them into critical thinking skill levels. The results showed that students' critical thinking skills were in the very low category with an average score of 15.93. The indicator with the highest achievement was advanced clarification, while the lowest indicator was strategy and tactics. These findings indicate that students still experience difficulties in conducting analysis, drawing conclusions, and determining problem-solving strategies